The Effectiveness of Problem Based Learning Model and Quizizz Application in Improving Learning Outcomes and Motivation - Lestari, Dwita; Widyaningrum, Indah; Susanti, Novi (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to identify the influence of the use of problem-based learning models (PBL) combined with the Quizizz application on learning outcomes and student motivation in trigonometry material in class X of SMA Muhammadiyah Pagaralam. This study uses an experimental method with a Pretest-Posttest design Control Group. The research sample consisted of students of class X MIPA 3 as the experimental class and students of class X MIPA 2 as the control class, each consisting of 36 students. Data were collected through test and documentation methods using descriptive questions as instruments. The results of the study showed that students who learned using the Problem Based learning model Learning combined with the Quizizz application has better learning outcomes than students who follow conventional learning. This shows that the innovative learning approach is able to increase the effectiveness of learning in trigonometry material.